Needs of older adults in Kazakhstan: analysis and psychometric properties of the localized version of the EASYCare standard 2010 instrument - Kimatova, Kerbez; Yermukhanova, Lyudmila; Talarska, Dorota; Dworacka, Marzena; Sultanova, Gulnar; Sarsenbayeva, Gulzat; Bazargaliyev, Yerlan; Aitmaganbet, Perizat; Suwalska, Aleksandra; Wieczorowska-Tobis, Katarzyna; Philp, Ian; Tobis, Slawomir (Frontiers in Public Health, 2025)
BackgroundStudies about the needs of older individuals in Central Asia are very sparse. Thus, this study aimed to evaluate the needs of older adults in Kazakhstan with the EASYCare Standard 2010 (EC) questionnaire.MethodsThe study involved 524 participants aged 65 and older from various regions in Kazakhstan. Data were collected by trained research staff, and the participants’ needs were examined using median split with the three summarizing indexes of the EC system (Independence score, Risk of breakdown in care, and Risk of falls).ResultsSubjects with primary education had approximately double odds of scoring above the median compared to those with higher education in Independence score (p < 0.01) and Risk of breakdown in care (p < 0.01). Individuals with primary education also had 60% higher odds of scoring above the Risk of falls scale threshold, indicating a risk in this category (p < 0.05). For the Risk of falls scores, financial situation was also significant; individuals having not enough to make ends meet had 75% higher odds than the remaining ones (p < 0.01).ConclusionOur analysis highlights the importance of tailored interventions to address the unmet needs of the Kazakh population, particularly among those with lower education and those with financial concerns. The study also underscores the need for sustainable, comprehensive eldercare policies in Kazakhstan that account for the growing older population.